Caracterização e comparação de lesões na coluna toracolombar de equinos com e sem laminite crônica - Julia Renault Baeta Guedes (2023)
Laminitis is the second leading cause of death in horses and the most debilitating disease that affects the distal part of the locomotor apparatus. Due to the intense pain that is mainly manifested in the thoracic limbs, the affected horse displaces its trunk caudally, adopting a constant posture of arched back and flexed thoracolumbar spine. The possible repercussions of such posture on the vertebral column of horses are not yet known or explored. The aim of this study is to investigate the prevalence and intensity of injuries that affect the thoracolumbar spine in horses with laminitis, comparing them with those of healthy horses. A population sample of 60 horses was used, 30 clinically healthy and 30 with chronic laminitis, composed of 42 females and 18 males of different breeds, various functions and aged between 2 and 20 years from Minas Gerais, São Paulo and Paraná. The animals were evaluated on a single occasion, using physical examination and a score system for injuries determined by inspection tests, palpation and mobility tests in the spine called the Clinical Assessment Method of the Equine Thoracolumbar Spine (MACCTORE), which was developed in this experiment. Additionally, the Equine Grimace Scale (HGS) was applied to assess pain, and ultrasound assessment of the thoracolumbar spine was performed transversely from the T17-L6 region with the convex probe and longitudinally from the T5-L6 region with the linear probe. The ultrasound images were assessed by 2 different blinded assessors. Muscle function was also assessed by determining the blood concentrations of muscle enzymes. The values of each variable were compared between groups by the unpaired Student's t-test or Mann-Whitney test (P<0.05). Furthermore, the frequency distribution of affected animals with injury scores above and below the cutoff point, which corresponded to the 75th percentile (P75) of the entire population, was compared. Horses with chronic laminitis showed a higher pain manifestation (HGS and heart rate frequency P<0.0001) concomitant with significant increases in the means (±SD) of the thoracolumbar spine injury rates both in the MACCTORE clinical examination (11.7±4.8 vs. 4.2±3.3, P<0.0001) and overall ultrasound index (39.6±12.0 vs. 20.7±7.1, P<0.0001) and in specific examinations for articular and spinous processes (P<0.0001), supraspinous ligament (P=0.0003) and epaxial muscle (P=0.017). Based on the pre-established parameters (total US grade > 30), horses with laminitis showed a 14 times higher prevalence (CI: 4.4 to 50.6, P<0.0001) of relevant ultrasound injuries in the thoracolumbar spine. Although primary, the results are sufficient to demonstrate a significant association between chronic laminitis and the occurrence of injuries in the lumbar spine of horses. New efforts are urgently needed to expand the characterization of the injuries demonstrated here and to propose specific preventive and therapeutic measures for the vertebral spine that provide greater effectiveness in the rehabilitation and well-being of horses with chronic laminitis.